The other people : a novel - Tudor, C. J. (Ballantine Books, 2020)
Driving home one night, stuck behind a rusty old car, Gabe sees a little girl<U+2019>s face appear in its rear window. She mouths one word: Daddy. It<U+2019>s his five-year-old daughter, Izzy. He never sees her again. Three years later, Gabe spends his days and nights traveling up and down the highway, searching for the car that took his daughter, refusing to give up hope, even though most people believe she<U+2019>s dead. When the car that he saw escape with his little girl is found abandoned with a body inside, Gabe must confront not just the day Izzy disappeared but the painful events from his past now dredged to the surface. Fran and her daughter, Alice, also put in a lot of miles on the road. Not searching. Running. Because Fran knows what really happened to Gabe<U+2019>s daughter. She knows who is responsible. And she knows what they will do if they ever catch up to her and Alice.